A Miniature Microstrip Antenna Array using Circular Shaped Dumbbell for ISM Band Applications - Ahmed Ghaloua; Jamal Zbitou; Larbi El Abdellaoui; Mohamed Latrach; Ahmed Errkik; Abdelali Tajmouati (Institute of Advanced Engineering and Science, 2018)
The aim of this work is the achievement, and the validation of a small microstrip patch antenna array using a circular shaped dumbbell defected ground structure. This work has been dividing into two stages: The first step is to miniaturize a microstrip patch antenna resonating at 5.8GHz, which operate in the Industrial Scientific Medical band (ISM) and the second is to use a circular defected ground structure to shift the resonance frequency of the antenna array from 5.8GHz to 2.45GHz. At last, a miniaturization up to 74.47%, relative to the original microstrip antenna array has accomplished. The antenna structure has designed, optimized and miniaturized using CST MW Studio. The obtained results have compared with Ansoft’s HFSS electromagnetic solver. The antenna array has fabricated on FR-4 substrate, and its reflection coefficient is measured.